(untitled) (Northern International Medical College Journal, 2015)
Background : Good health is a marker of good economic status of a nation. Personal hygiene should be maintained first for obtaining great accuracy in work, low suffering from diseases and to reduce possibility of diseases. Objective : This study was undertaken to assess practice of personal hygiene among rural women of a selected community in Bangladesh. Materials & Methods : A descriptive type of cross sectional study was conducted during MarchJune 2012. 150 women of various ages selected from Garibpur and Tangurpur villages of Jessore District to assess two basic components of personal hygiene, hand washing and safe drinking water. Non probability convenient sampling technique was followed and data were collected by face to face interview using pre tested, self administered, semi structured questionnaire. Results : The mean age of the respondents was 33 years. Regarding educational qualification, 87.33% were educated in different levels and 12.67% were illiterate. Occupational status revealed majority (74.67%) of them were housewives. Regarding economic condition, most (60%) of the respondents had family income <10,000 Taka. In this study, majority (87.34%) had practiced hand washing before eating. Among them on taking different types of food (86.26%) practiced hand washing before taking meals only 13.74% before taking breakfast and none of the respondents washed hands before taking any dry food. Majority (95.34%) practiced hand washing after defecation, among them (82%) used soap, 16% used ash and 2% used soil after defecation. In this study, majority (90.67%) used tube well which was not marked red, 6% used pond and 3.33% used river as their source of drinking water. Conclusion : Good practice of personal hygiene and use of safe drinking water has significant importance to lead a healthy life, the villagers of Bangladesh should be well motivated regarding this aspect by regular health education programmes. Northern International Medical College Journal Vol.6(1) 2014: 29-31